A Seamless Healthcare System Management: Keys to Success in 4 Countries - Mookdadilok, Orapin (Journal of Health Science of Thailand, 2017)
A correlation of the experiences of Thailand and other countries revealed four key factors to a successful healthcare system that is seamlessly interconnected at every level, be it primary, secondary, or tertiary. First, the introduction of a mindset and culture in which the population seeks appropriate health care at each level. Second, the creation of a basic infrastructure at the secondary- and tertiary-care levels which seamlessly integrates the healthcare and information networks at every level and in every area. Third, the provision of quality services that make use of existing resources outside of the second- and tertiary-care settings. And lastly, the overhaul of the management of specialized hospitals so they can function smoothly, with the state retaining ownership and the private sector providing primary health care.